2017
DOI: 10.1002/nme.5628
|View full text |Cite
|
Sign up to set email alerts
|

The diffuse Nitsche method: Dirichlet constraints on phase‐field boundaries

Abstract: Summary We explore diffuse formulations of Nitsche's method for consistently imposing Dirichlet boundary conditions on phase‐field approximations of sharp domains. Leveraging the properties of the phase‐field gradient, we derive the variational formulation of the diffuse Nitsche method by transferring all integrals associated with the Dirichlet boundary from a geometrically sharp surface format in the standard Nitsche method to a geometrically diffuse volumetric format. We also derive conditions for the stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(61 citation statements)
references
References 79 publications
1
60
0
Order By: Relevance
“…This choice resulted in stable finite element computations in all simulations, while an influence of the stabilization term on the convergence behavior could not be observed in the numerical tests. For more information on accuracy, convergence, and stabilization, interested readers are referred to the computational study in the Appendix and further results reported in Nguyen et al 61 that focuses on the diffuse Nitsche method from a numerical analysis viewpoint. In particular, the latter provides a generalization of the eigenvalue-based estimation of the stabilization parameter and a comparison with consistent penalty-type methods derived, for example, in Li et al 27…”
Section: Dirichlet Boundary Conditionsmentioning
confidence: 99%
“…This choice resulted in stable finite element computations in all simulations, while an influence of the stabilization term on the convergence behavior could not be observed in the numerical tests. For more information on accuracy, convergence, and stabilization, interested readers are referred to the computational study in the Appendix and further results reported in Nguyen et al 61 that focuses on the diffuse Nitsche method from a numerical analysis viewpoint. In particular, the latter provides a generalization of the eigenvalue-based estimation of the stabilization parameter and a comparison with consistent penalty-type methods derived, for example, in Li et al 27…”
Section: Dirichlet Boundary Conditionsmentioning
confidence: 99%
“…A phase field function ϕ is defined as an approximation to the step function to represent a diffuse boundary as illustrated in Figure 1. The volume integral over a function Q can be written as 16‐18 ΩQ0.1emdnormalΩ=normalΩ0italicQH0.1emdΩ0normalΩ0italicQϕ0.1emdΩ0. …”
Section: Methodsmentioning
confidence: 99%
“…In order to consider the boundary conditions on a surface Γ, the Dirac distribution δ Γ is approximated by the absolute gradient of the phase field function. A diffuse boundary integral of a function h over a boundary Γ is modeled as follows 16,18 : Γh0.1emdnormalΓ=normalΩ0hδΓ0.1emdnormalΩnormalΩ0hϕ0.1emdnormalΩ. …”
Section: Methodsmentioning
confidence: 99%
“…( 1) are evaluated the method's effectiveness crucially depends on the choice of β. From other works [34] it is also clear that the diffuse interface approach is very sensitive to the choice of . Hence a numerical study is now considered that allows to characterize the influence of β on the resulting error while considering in the diffuse interface approach.…”
Section: Annular Plate Benchmarks 311 Problem Definitionmentioning
confidence: 98%